Preparation method of monodisperse ultra-small nano copper oxide liquid-phase dispersion
Through copper salt hydrolysis reaction and surface modifier modification, the size and stability of copper oxide particles were solved, and a nano copper oxide liquid phase dispersion that was uniformly dispersed in different solvents was prepared, achieving simplification of the process and environmental protection. , suitable for industrial production.
Patent Information
- Application Number
- CN202310869706.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-14
AI Technical Summary
In the existing copper oxide preparation process, the particles are large, the size distribution is uneven, and the stable dispersion in the solvent cannot be stable, and the process is complicated, making it difficult to prepare ultra-small nano copper oxide dispersions.
Using the hydrolysis reaction of copper salt, combined with the modification of the surface modifier, a monodispersed ultra-small nano copper oxide liquid phase dispersion with regular morphology and uniform size distribution can be prepared, which can be stablely dispersed in different solvents, and the process Simple, green and environmentally friendly.
The preparation of monodispersed copper oxide nanoparticles in the range of 1-5nm is achieved. The product remains stable after being left to stand for a long time. It is suitable for industrial large-scale production and provides a variety of application prospects.
Smart Images

Figure CN119306246A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanoparticle preparation; more specifically, to a method for preparing a monodisperse ultra-small nano copper oxide liquid phase dispersion. Background Art
[0002] Copper oxide (CuO) is a hot research topic among transition metal oxides because it is a p-type semiconductor with a narrow bandgap (1.2 eV in bulk) and is the fundamental magnetoresistive material for several high-temperature superconductors and giant materials. CuO nanostructures with large surface area and potential size effect have superior physical and chemical properties that are significantly different from their micro or bulk counterparts. These nanostructures have been widely studied for their promising applications in various fields. CuO nanostructures are widely used in the fields of antibacterial, gas sensors, biosensors, nanofluids, photodetectors, high-energy materials, supercapacitors, removal of inorganic pollutants, photocatalysis, and magnetic storage media. In addition, nanoscale CuO can also be used to prepare a variety of organic-inorganic nanocomposites with high thermal conductivity, high electrical conductivity, high mechanical strength, high temperature resistance, etc.
[0003] In recent years, there have been a variety of different technologies used for the preparation of nano copper oxide, including direct precipitation, solvent thermal method, microemulsion method, sol-gel method, electrochemical deposition and other methods, and different methods have different advantages and disadvantages. For example, Chinese invention patent application CN113247942A discloses a method for preparing nano copper oxide, the steps of which include: mixing copper nitrate solution and sodium carbonate solution and stirring evenly to obtain a blue suspension; transferring the mixed solution into a polytetrafluoroethylene reactor, placing it in an oven and heating it to 120°C for reaction for 6 hours, then cooling it to room temperature, heating it to 140°C, reacting it for 3 hours, then cooling it to room temperature, heating it to 160°C, reacting it for 3 hours, cooling it to room temperature and then taking it out; opening the polytetrafluoroethylene reactor, taking out the mixed solution, washing it alternately with anhydrous ethanol and deionized water for several times, and then centrifuging it to obtain a precipitate, and drying the precipitate in an oven at 80°C for 5 hours to obtain nano copper oxide powder. The invention's nano copper oxide preparation method is simple, has good crystal form, and is prepared together with activated carbon to obtain a nano copper oxide activated carbon catalyst, which can denitrate flue gas at low temperature without heating the flue gas, and the denitration rate is about 72%, which is much higher than other catalysts. However, the preparation process of the patented method is cumbersome, the time cost is high, and the diameter of the product copper oxide is too large, close to the micron level, and cannot be stably dispersed in the solvent.
[0004] At present, the research on the preparation process of copper oxide generally has problems such as large particles, uneven size distribution, inability to disperse stably in solvents, easy sedimentation, or regular morphology but generally cumbersome preparation process. How to overcome this problem and use a simple preparation process to prepare a nano copper oxide dispersion with a smaller size that can be stably dispersed in different solvents is one of the problems to be solved. So far, there has been no relevant report on ultra-small nano copper oxide dispersions. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing a monodisperse ultra-small nano copper oxide liquid phase dispersion. The ultra-small nano copper oxide prepared by the method through the hydrolysis reaction of copper salt can be dispersed into different dispersants by utilizing the modification effect of different surface modifiers, with good dispersion effect and no sedimentation after standing for ≥6 months; the method can obtain a monodisperse copper oxide nano dispersion with regular morphology, uniform size distribution and particle size maintained at 1-5nm. Compared with the traditional preparation method, this method does not require high-temperature hydrothermal or calcination, is green and environmentally friendly, has a simple process, and is easy to realize industrial large-scale production. Liquid phase dispersions of different dispersants can provide more application value and have good application prospects.
[0006] To solve the above technical problems, the technical solutions adopted are as follows: :
[0007] A method for preparing a monodisperse ultrasmall nano copper oxide liquid phase dispersion comprises the following steps:
[0008] 1) dissolving a copper salt precursor in a solvent to prepare a copper salt solution; dissolving an alkali in a solvent to prepare an alkali source solution; dissolving a surface modifier in a solvent to prepare a surface modifier solution;
[0009] 2) mixing the copper salt solution and the alkali source solution to perform a hydrolysis reaction until the reaction solution turns black;
[0010] 3) adding a surface modifier solution into the reaction solution for modification to obtain modified nano copper oxide particles;
[0011] 4) The modified rice copper oxide particles are centrifugally washed and then dispersed in different solvents to obtain a monodisperse ultra-small nano copper oxide liquid phase dispersion.
[0012] As a further improvement of the technical solution, in step 1), the copper salt is selected from one or more of copper chloride, copper acetate, copper nitrate, copper sulfate, and copper acetylacetonate.
[0013] Preferably, in step 1), the concentration of the copper salt precursor solution is 0.05-0.5 mol / L; preferably, the concentration of the copper salt precursor solution is 0.2-0.5 mol / L.
[0014] Preferably, in step 1), the alkali source is selected from one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, ammonia water and urea.
[0015] Preferably, in step 1), the concentration of the alkali source solution is 0.1-1 mol / L; preferably, the concentration of the alkali source solution is 0.4-1 mol / L.
[0016] Preferably, in step 1), the surface modifier is selected from one or more of polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide, polyethylene glycol, citric acid, sodium citrate, sodium dodecyl sulfate, phenyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-aminoethyl-γ-aminopropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, decanoic acid, lauric acid, myristic acid, stearic acid, behenic acid, oleic acid, sodium laurate, sodium stearate, and sodium oleate.
[0017] Preferably, in step 1), the mass ratio of the surface modifier to the product is 10wt.%-300wt.%; preferably, the mass ratio of the surface modifier to the product is 30wt.%-200wt.%.
[0018] Preferably, in step 1), the copper salt solution solvent is selected from one or more of water, methanol, ethanol, n-propanol, isopropanol, n-butanol, n-hexanol, n-octanol, acetone, ethylene glycol, glycerol, benzyl alcohol, n-hexane, cyclohexane, toluene, tetrahydrofuran, pyridine, ethyl acetate, and N-dimethylformamide.
[0019] Preferably, in step 1), the alkali source solution solvent is selected from one or more of water, methanol, ethanol, n-propanol, isopropanol, n-butanol, n-hexanol, n-octanol, acetone, ethylene glycol, glycerol, benzyl alcohol, n-hexane, cyclohexane, toluene, tetrahydrofuran, pyridine, ethyl acetate, and N-dimethylformamide.
[0020] Preferably, in step 1), the surface modifier solution solvent is selected from one or more of water, methanol, ethanol, n-propanol, isopropanol, n-butanol, n-hexanol, n-octanol, acetone, ethylene glycol, glycerol, benzyl alcohol, n-hexane, cyclohexane, toluene, tetrahydrofuran, pyridine, ethyl acetate, and N-dimethylformamide.
[0021] Preferably, in step 1), the copper salt solution also includes a doping metal salt; the doping metal salt is selected from one or more of the following substances: lanthanum nitrate, gadolinium nitrate, cerium nitrate, yttrium nitrate, neodymium nitrate, scandium nitrate, zinc nitrate, magnesium nitrate, magnesium chloride, cobalt nitrate, nickel chloride, ferric chloride, ferrous chloride, ferrous sulfate heptahydrate, cerium nitrate hexahydrate, and cerium acetate.
[0022] Preferably, in step 1), the molar percentage of the doped metal salt in the copper salt precursor is 0.5-10%; preferably, the molar percentage of the doped metal salt in the copper salt precursor is 3-10%.
[0023] As a further improvement of the technical solution, in step 2), the reaction temperature of the copper salt solution and the alkali source solution is 40-100°C; preferably, the reaction temperature is 60-100°C. ;
[0024] Preferably, in step 2), the reaction time is 1-15 min; preferably, the reaction time is 3-10 min.
[0025] As a further improvement of the technical solution, in step 3), the modification temperature of the surface modifier is 40-100°C; preferably, the modification temperature is 60-100°C;
[0026] Preferably, in step 3), the modification time is 20-120 min; preferably, the modification time is 30-60 min.
[0027] As a further improvement of the technical solution, in step 4), the centrifugal speed is 5000-12000 rpm; preferably, the centrifugal speed is 6000-10000 rpm.
[0028] Preferably, in step 4), the centrifugation time is 3-15 min; preferably, the centrifugation time is 5-10 min.
[0029] Preferably, in step 4), the dispersant is selected from one or more of the following substances: water, methanol, ethanol, n-propanol, ethylene glycol, glycerol, NN dimethylformamide, cyclohexane, n-hexane, toluene, xylene, petroleum ether 30-60°C, petroleum ether 60-90°C, dichloromethane, chloroform, tetrahydrofuran, naphtha, white oil, diesel, fish oil, methyl methacrylate, ethyl acetate, butyl acetate, acetone, cyclohexanone, methyl isobutyl ketone, and castor oil.
[0030] Any range described in the present invention includes the end value and any numerical value between the end values and any sub-range formed by the end value or any numerical value between the end values.
[0031] Unless otherwise specified, all raw materials in the present invention can be purchased from the market, and the equipment used in the present invention can adopt conventional equipment in the relevant field or refer to the existing technology in the relevant field.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The present invention uses a method for hydrolyzing copper salt to obtain a monodisperse nano-copper oxide liquid phase dispersion with controllable morphology, uniform arrangement, narrow particle size distribution, and particle size ≤5nm; the obtained product can remain stable after standing for a long time (≥6 months), and the solid content of the product is 1wt.%-30wt.%.
[0034] 2. The nano copper oxide liquid phase dispersion prepared by the present invention can be prepared into a liquid phase dispersion with water or a plurality of organic solvents or a mixture thereof as a dispersant by changing the type of the surface modifier. Different dispersants can be selected according to practical applications, and it has a wide range of application value;
[0035] 3. The preparation process of the present invention does not require high-temperature hydrothermal treatment, has a simple preparation process, a short reaction time, mild conditions, is green, clean and environmentally friendly, and is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The specific embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.
[0037] Figure 1 The TEM of the product obtained in Example 1 of the present invention is shown;
[0038] Figure 2 The XRD of the product obtained in Example 2 of the present invention is shown;
[0039] Figure 3 The figure shows the appearance of the product obtained in Example 4 of the present invention after being left to stand for 6 months;
[0040] Figure 4 A schematic structural diagram of the supergravity rotating packed bed reactor used in Example 14 of the present invention is shown. DETAILED DESCRIPTION
[0041] In order to explain the present invention more clearly, the present invention is further described below in conjunction with embodiments. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0042] As one aspect of the present invention, a method for preparing a monodisperse ultrasmall nano copper oxide liquid phase dispersion comprises the following steps:
[0043] 1) dissolving a copper salt precursor in a solvent to prepare a copper salt solution; dissolving an alkali in a solvent to prepare an alkali source solution; dissolving a surface modifier in a solvent to prepare a surface modifier solution;
[0044] 2) mixing the copper salt solution and the alkali source solution to undergo a hydrolysis reaction until the reaction solution turns black;
[0045] 3) adding a surface modifier solution into the reaction solution for modification to obtain modified nano copper oxide particles;
[0046] 4) The modified rice copper oxide particles are centrifugally washed and then dispersed in different solvents to obtain a monodisperse ultra-small nano copper oxide liquid phase dispersion.
[0047] In the present invention, the preparation principle of copper oxide is based on Cu 2+ Hydrolysis under alkaline conditions further decomposes into CuO; the reaction equation is as follows:
[0048] Cu 2+ +4OH - →Cu(OH)4 2- →CuO+H2O+2OH -
[0049] The reaction rate is fast, and no intermediate product Cu(OH)2 is generated. Compared with the traditional copper oxide preparation method, the preparation of copper oxide based on this principle does not require high-temperature calcination and hydrothermal treatment, and the reaction can occur at a temperature of 40-100°C. In addition, due to its fast reaction rate, ultra-small nanoparticles can be prepared, providing an important basis for subsequent dispersion research.
[0050] In certain embodiments of the present invention, in step 1), the copper salt is selected from one or more of copper chloride, copper acetate, copper nitrate, copper sulfate, and copper acetylacetonate.
[0051] In certain embodiments of the present invention, in step 1), the concentration of the copper salt precursor solution is 0.05-0.5 mol / L; preferably, the concentration of the copper salt precursor solution is 0.2-0.5 mol / L.
[0052] In certain embodiments of the present invention, in step 1), the alkali source is selected from one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, ammonia water, and urea.
[0053] In certain embodiments of the present invention, in step 1), the concentration of the alkali source solution is 0.1-1 mol / L; preferably, the concentration of the alkali source solution is 0.4-1 mol / L.
[0054] In certain embodiments of the present invention, in step 1), the molar ratio of the copper salt to the alkali salt is 0.4-0.6, preferably, the molar ratio of the copper salt to the alkali salt is 0.45-0.55.
[0055] In certain embodiments of the present invention, in step 1), the surface modifier is selected from one or more of polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide, polyethylene glycol, citric acid, sodium citrate, sodium dodecyl sulfate, phenyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-aminoethyl-γ-aminopropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, decanoic acid, lauric acid, myristic acid, stearic acid, behenic acid, oleic acid, sodium laurate, sodium stearate, and sodium oleate.
[0056] In certain embodiments of the present invention, in step 1), the mass ratio of the surface modifier to the product is 10wt.%-300wt.%; preferably, the mass ratio of the surface modifier to the product is 30wt.%-200wt.%.
[0057] In certain embodiments of the present invention, in step 1), the copper salt solution solvent is selected from one or more of water, methanol, ethanol, n-propanol, isopropanol, n-butanol, n-hexanol, n-octanol, acetone, ethylene glycol, glycerol, benzyl alcohol, n-hexane, cyclohexane, toluene, tetrahydrofuran, pyridine, ethyl acetate, and N-dimethylformamide.
[0058] In certain embodiments of the present invention, in step 1), the alkali source solution solvent is selected from one or more of water, methanol, ethanol, n-propanol, isopropanol, n-butanol, n-hexanol, n-octanol, acetone, ethylene glycol, glycerol, benzyl alcohol, n-hexane, cyclohexane, toluene, tetrahydrofuran, pyridine, ethyl acetate, and N-dimethylformamide.
[0059] In certain embodiments of the present invention, in step 1), the surface modifier solution solvent is selected from one or more of water, methanol, ethanol, n-propanol, isopropanol, n-butanol, n-hexanol, n-octanol, acetone, ethylene glycol, glycerol, benzyl alcohol, n-hexane, cyclohexane, toluene, tetrahydrofuran, pyridine, ethyl acetate, and N-dimethylformamide.
[0060] In certain embodiments of the present invention, in step 1), the copper salt solution further includes a doping metal salt; the doping metal salt is selected from one or more of the following substances: lanthanum nitrate, gadolinium nitrate, cerium nitrate, yttrium nitrate, neodymium nitrate, scandium nitrate, zinc nitrate, magnesium nitrate, magnesium chloride, cobalt nitrate, nickel chloride, ferric chloride, ferrous chloride, ferrous sulfate heptahydrate, cerium nitrate hexahydrate, and cerium acetate.
[0061] In certain embodiments of the present invention, in step 1), the molar percentage of the doped metal salt in the copper salt precursor is 0.5-10%; preferably, the molar percentage of the doped metal salt in the copper salt precursor is 3-10%.
[0062] In certain embodiments of the present invention, in step 2), the reaction temperature of the copper salt solution and the alkali source solution is 40-100°C; preferably, the reaction temperature is 60-100°C.
[0063] In certain embodiments of the present invention, in step 2), the reaction time is 1-15 min; preferably, the reaction time is 3-10 min.
[0064] In certain embodiments of the present invention, in step 3), the modification temperature of the surface modifier is 40-100°C; preferably, the modification temperature is 60-100°C.
[0065] In certain embodiments of the present invention, in step 3), the modification time is 20-120 min; preferably, the modification time is 30-60 min.
[0066] In certain embodiments of the present invention, in step 4), the centrifugal speed is 5000-12000 rpm; preferably, the centrifugal speed is 6000-10000 rpm.
[0067] In certain embodiments of the present invention, in step 4), the centrifugation time is 3-15 min; preferably, the centrifugation time is 5-10 min.
[0068] In certain embodiments of the present invention, in step 4), the dispersant is selected from one or more of the following substances: water, methanol, ethanol, n-propanol, ethylene glycol, glycerol, NN dimethylformamide, cyclohexane, n-hexane, toluene, xylene, petroleum ether 30-60°C, petroleum ether 60-90°C, dichloromethane, chloroform, tetrahydrofuran, naphtha, white oil, diesel, fish oil, methyl methacrylate, ethyl acetate, butyl acetate, acetone, cyclohexanone, methyl isobutyl ketone, and castor oil.
[0069] Example 1
[0070] A method for preparing a monodispersed nano copper oxide methanol phase dispersion comprises the following steps:
[0071] 1) Dissolve 3.5 g of copper acetate monohydrate in 50 mL of ethanol solvent to prepare a copper acetate solution;
[0072] Dissolve 1.4 g of sodium hydroxide in 50 mL of ethanol to prepare a sodium hydroxide solution;
[0073] Dissolve 1.5 g of N-aminoethyl-γ-aminopropyltrimethoxysilane in 30 mL of ethanol to prepare an N-aminoethyl-γ-aminopropyltrimethoxysilane solution;
[0074] 2) Adding sodium hydroxide solution to copper acetate solution at a constant temperature of 40°C to carry out hydrolysis reaction and stirring for 10 minutes;
[0075] 3) slowly adding N-aminoethyl-γ-aminopropyltrimethoxysilane solution into the reaction solution for modification, heating to 60° C. for modification for 20 min, to obtain modified nano copper oxide particles;
[0076] 4) The modified nano copper oxide particles were separated from the reaction solvent by centrifugation at 12000 rpm for 15 minutes, and washed three times by centrifugation with water. The obtained precipitate was dispersed in methanol solvent to obtain a monodisperse ultra-small nano copper oxide methanol phase dispersion.
[0077] Figure 1 This is a transmission electron micrograph of the monodisperse ultrasmall nano copper oxide methanol phase dispersion prepared in Example 1.
[0078] It can be seen from the figure that copper oxide is monodisperse and has regular morphology, uniform size distribution, particle size of 1-5nm, and an average particle size of 3nm.
[0079] Example 2
[0080] A method for preparing a monodisperse nano copper oxide aqueous dispersion comprises the following steps:
[0081] 1) Dissolve 4.5 g of copper acetate monohydrate in a mixed solvent of 50 mL of methanol and 10 mL of water to prepare a copper acetate solution;
[0082] Dissolve 2.5 g of potassium hydroxide in a mixed solvent of 45 mL of methanol and 15 mL of water to prepare a potassium hydroxide solution;
[0083] 1.1 g of 3-aminopropyltrimethoxysilane was dissolved in 15 mL of ethanol to prepare a 3-aminopropyltrimethoxysilane solution;
[0084] 2) Pour the potassium hydroxide solution into the copper acetate solution at a constant temperature of 70°C for hydrolysis reaction and stir for 15 minutes;
[0085] 3) slowly adding 3-aminopropyltrimethoxysilane solution into the reaction solution for modification, heating to 80° C. for modification for 120 min, to obtain modified nano copper oxide particles;
[0086] 4) The modified nano copper oxide particles were separated from the reaction solvent by centrifugation at 5000 rpm for 3 minutes, and washed three times by centrifugation with ethanol. The obtained precipitate was dispersed in an aqueous solvent to obtain a monodisperse ultra-small nano copper oxide aqueous dispersion.
[0087] Figure 2 This is the XRD pattern of the monodisperse ultra-small nano copper oxide aqueous dispersion prepared in Example 2. It matches the PDF standard card, proving that copper oxide is prepared.
[0088] After testing, the copper oxide prepared in this example is monodisperse and has a regular morphology, a uniform size distribution, a particle size of 1-5 nm, and an average particle size of 3.2 nm.
[0089] Example 3
[0090] A method for preparing a monodisperse nano copper oxide aqueous dispersion comprises the following steps:
[0091] 1) Dissolve 2.8 g of copper sulfate pentahydrate and 2.7 g of polyvinyl pyrrolidone in a mixed solvent of 30 mL of ethanol and 30 mL of water to prepare a copper acetate modified solution; dissolve 1.05 g of sodium hydroxide in a mixed solvent of 30 mL of methanol and 15 mL of propanol to prepare a sodium hydroxide solution;
[0092] 2) adding sodium hydroxide solution to copper acetate solution at a constant temperature of 60° C. to carry out hydrolysis reaction, stirring the reaction for 60 minutes, and obtaining modified nano copper oxide particles;
[0093] 3) The modified nano copper oxide particles were separated from the reaction solvent by centrifugation at 12000 rpm for 10 minutes, and washed three times by centrifugation with 1:1 ethanol and water. The obtained precipitate was dispersed in an aqueous solvent to obtain a monodisperse ultra-small nano copper oxide aqueous dispersion.
[0094] After testing, the copper oxide prepared in this example is monodispersed and has a regular morphology, a uniform size distribution, a particle size of 2-4 nm, and an average particle size of 3.1 nm.
[0095] It can be seen that the preparation steps in the present invention are not fixed. The copper salt and the surface modifier can be dissolved in a solvent at the same time, and then an alkaline solution is added, and the hydrolysis reaction and modification are carried out simultaneously.
[0096] Example 4
[0097] A method for preparing a monodisperse nano-copper oxide cyclohexane phase dispersion comprises the following steps:
[0098] 1) Dissolve 4.0 g of cupric chloride dihydrate in 50 mL of methanol solvent to prepare a cupric chloride solution; dissolve 2.1 g of sodium hydroxide in 50 mL of methanol to prepare a sodium hydroxide solution; dissolve 0.8 g of oleic acid in 25 mL of methanol to prepare an oleic acid solution;
[0099] 2) adding sodium hydroxide solution to cupric chloride solution at a constant temperature of 60°C for hydrolysis reaction and stirring for 10 minutes;
[0100] 3) slowly adding oleic acid solution into the reaction solution for modification at 60° C. for 30 min to obtain modified nano copper oxide particles;
[0101] 4) adding water to the modified nano copper oxide particles to precipitate the nano particles from the reaction solution, separating them by centrifugation at 5000 rpm for 5 minutes, washing them by centrifugation three times with ethanol, removing the residual water and reaction solvent in the reaction precipitate by rotary evaporation, and dispersing the obtained precipitate in cyclohexane to obtain a monodisperse nano copper oxide cyclohexane phase dispersion.
[0102] Figure 3 This is a physical picture of the monodisperse ultra-small nano copper oxide cyclohexane phase dispersion prepared in Example 4. It can be seen that the dispersion is stably dispersed and does not precipitate after being placed for more than 6 months;
[0103] After testing, the copper oxide prepared in this example is monodisperse and has a regular morphology, a uniform size distribution, a particle size of 2-5 nm, and an average particle size of 3.3 nm.
[0104] Example 5
[0105] A method for preparing a monodisperse zinc-doped nano-copper oxide cyclohexane phase dispersion comprises the following steps:
[0106] 1) Dissolve 3.5 g of copper nitrate trihydrate and 0.022 g of zinc nitrate hexahydrate in a mixed solvent of 180 mL of ethanol and 110 mL of methanol to prepare a metal precursor solution; dissolve 1.6 g of potassium hydroxide in a mixed solvent of 125 mL of methanol and 125 mL of isopropanol to prepare a potassium hydroxide solution; dissolve 0.75 g of stearic acid in 30 mL of ethanol to prepare a stearic acid solution;
[0107] 2) Pour potassium hydroxide solution into the metal precursor solution at a constant temperature of 80°C for hydrolysis reaction and stir for 15 minutes;
[0108] 3) slowly adding stearic acid solution into the reaction solution for modification, modifying at 80° C. for 120 min to obtain modified zinc-doped nano copper oxide particles;
[0109] 4) adding water to the modified zinc-doped nano-copper oxide particles to precipitate the nano-particles from the reaction solution, separating them by centrifugation at 5000 rpm for 5 minutes, washing them by centrifugation three times with ethanol, removing the residual water and reaction solvent in the reaction precipitate by rotary evaporation, and dispersing the obtained precipitate in cyclohexane to obtain a monodisperse ultra-small zinc-doped nano-copper oxide cyclohexane phase dispersion.
[0110] After testing, the zinc-doped nano-copper oxide prepared in this embodiment is monodispersed and has a regular morphology, a uniform size distribution, a particle size of 3-5 nm, and an average particle size of 4 nm.
[0111] Example 6
[0112] A method for preparing a monodisperse cerium-doped nano copper oxide aqueous dispersion comprises the following steps:
[0113] 1) Dissolve 10 g of copper acetate monohydrate and 2.2 g of cerium nitrate hexahydrate in 100 mL of water to prepare a metal precursor solution; dissolve 5.6 g of potassium hydroxide in 100 mL of water to prepare a potassium hydroxide solution; dissolve 0.4 g of 3-aminopropyltrimethoxysilane in 30 mL of ethanol to prepare a 3-aminopropyltrimethoxysilane solution;
[0114] 2) Pour potassium hydroxide solution into the metal precursor solution at a constant temperature of 100°C for hydrolysis reaction and stir for 5 minutes;
[0115] 3) slowly adding 3-aminopropyltrimethoxysilane solution into the reaction solution for modification at 100° C. for 120 min to obtain modified cerium-doped nano-copper oxide particles;
[0116] 4) The modified cerium-doped nano-copper oxide particles were separated from the reaction solvent by centrifugation at 5000 rpm for 3 minutes, and washed three times by centrifugation with ethanol. The obtained precipitate was dispersed in an aqueous solvent to obtain a monodisperse ultra-small cerium-doped nano-copper oxide aqueous dispersion.
[0117] After testing, the cerium-doped nano-copper oxide prepared in this embodiment is monodisperse and has a regular morphology, a uniform size distribution, a particle size of 3-5 nm, and an average particle size of 3.9 nm.
[0118] Example 7
[0119] Example 1 was repeated, except that in step 4), the precipitate obtained by centrifugation was dispersed in solvents such as ethanol, n-propanol, isopropanol, n-butanol, N-dimethylformamide, ethyl acetate, methyl formate, and methyl methacrylate, and dispersions in different solvents could be prepared. The dispersion effect was similar to that in Example 1.
[0120] Example 8
[0121] Example 2 was repeated, except that in step 4), a certain amount of ethylene glycol was added to the aqueous phase dispersion, and the water in the dispersion was removed by rotary evaporation to obtain a nano-copper oxide ethylene glycol phase dispersion, and the dispersion effect was similar to that of Example 2.
[0122] Example 9
[0123] Example 8 was repeated, except that ethylene glycol was replaced with glycerol to obtain a nano-copper oxide glycerol phase dispersion, and the dispersion effect was similar to that of Example 2.
[0124] Example 10
[0125] Example 4 was repeated, except that: in step 4), the precipitate obtained by centrifugation was dispersed in a solvent such as n-hexane, toluene, xylene, petroleum ether 30-60° C., petroleum ether 60-90° C., dichloromethane, chloroform, tetrahydrofuran, naphtha, white oil, diesel, fish oil, acetone, cyclohexanone, methyl isobutyl ketone, castor oil, etc., to prepare dispersions in different solvents, and the dispersion effect was similar to that in Example 4.
[0126] Embodiment 11
[0127] Example 1 was repeated, except that in step 1), the surface modifier was replaced with phenyltriethoxysilane or γ-methacryloxypropyltrimethoxysilane, and a methanol-phase nano-copper oxide dispersion was also obtained, and the dispersion effect was similar to that of Example 1.
[0128] Example 12
[0129] Example 2 was repeated, except that in step 1), the surface modifier was replaced with polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide, polyethylene glycol, citric acid, sodium citrate, sodium dodecyl sulfate, and 3-aminopropyltrimethoxysilane, and an aqueous nano-copper oxide dispersion was also obtained, and the dispersion effect was similar to that of Example 1.
[0130] Example 13
[0131] Example 4 was repeated, except that in step 1), the surface modifier was replaced with decanoic acid, lauric acid, myristic acid, stearic acid, behenic acid, sodium laurate, sodium stearate, and sodium oleate, and an aqueous nano-copper oxide dispersion was also obtained, and the dispersion effect was similar to that of Example 1.
[0132] Embodiment 14
[0133] The high gravity rotating packed bed reactor used in Examples 14 and 15 is a prior art, such as the high gravity rotating packed bed reactor used in the application document disclosed in the invention patent publication number CN2221437Y. Figure 4 As shown in the figure, the meanings of the numbers in the figure are: 1-copper solution feed port, 2-alkali solution feed port, 3-filler, 4-motor, 5-suspension outlet.
[0134] A method for preparing a monodispersed nano-copper oxide methanol phase dispersion using a high gravity rotating packed bed reactor comprises the following steps:
[0135] 1) Prepare liquid A: dissolve 10.1 g of copper acetate monohydrate in 150 mL of ethanol solvent and stir for 30 min; prepare liquid B: dissolve 5.5 g of potassium hydroxide in 150 mL of ethanol and stir for 30 min; prepare liquid C: dissolve 4.2 g of N-aminoethyl-γ-aminopropyltrimethoxysilane in 30 mL of ethanol and stir for 30 min;
[0136] 2) Adoption Figure 4 The device shown, start the circulating water device, set the water temperature to 70°C, and preheat the high gravity reactor;
[0137] 3) Turn on the ultra-gravity reaction device and set the rotation speed to 1500 rpm; turn on the feed pump to simultaneously deliver the feed liquid A and the feed liquid B to the rotating packed bed at a feed flow rate of 150 ml / min to react and obtain a reaction liquid;
[0138] 4) adding liquid C to the reaction solution for modification, and modifying in a constant temperature water bath at 60° C. for 45 minutes to obtain modified nano copper oxide particles;
[0139] 5) The modified nano copper oxide particles were separated from the reaction solvent by centrifugation at 12000 rpm for 15 minutes, and washed three times by centrifugation with water. The obtained precipitate was dispersed in methanol solvent to obtain a monodisperse ultra-small nano copper oxide methanol phase dispersion.
[0140] After testing, the copper oxide prepared in this example is monodisperse and has a regular morphology, a uniform size distribution, a particle size of 2-4 nm, and an average particle size of 3 nm.
[0141] Embodiment 15
[0142] A method for preparing a monodispersed nano copper oxide aqueous dispersion using a high gravity rotating packed bed reactor comprises the following steps:
[0143] 1) Prepare liquid A: dissolve 12.05 g of copper acetate monohydrate in 100 mL of methanol + 50 mL of water and stir for 30 min; prepare liquid B: dissolve 4.8 g of sodium hydroxide in 100 mL of methanol + 50 mL of water and stir for 30 min; prepare liquid C: dissolve 2 g of 3-aminopropyltrimethoxysilane in 30 mL of methanol and stir for 30 min;
[0144] 2) Adoption Figure 4 The device shown, start the circulating water device, set the water temperature to 70°C, and preheat the high gravity reactor;
[0145] 3) Turn on the supergravity reaction device and set the rotation speed to 1000 rpm. Turn on the feed pump to simultaneously deliver the feed liquid A and the feed liquid B to the rotating packed bed at a feed flow rate of 200 ml / min to react and obtain a reaction liquid.
[0146] 4) Slowly adding liquid C into the reaction solution for modification, and performing modification by external circulation in a supergravity reactor for 15 minutes to obtain modified nano copper oxide particles;
[0147] 5) The modified nano copper oxide particles were separated from the reaction solvent by centrifugation at 12000 rpm for 15 minutes, and washed three times by centrifugation with ethanol. The obtained precipitate was dispersed in water to obtain a monodisperse ultra-small nano copper oxide aqueous dispersion.
[0148] After testing, the copper oxide prepared in this example is monodisperse and has a regular morphology, a uniform size distribution, a particle size of 1-5 nm, and an average particle size of 2.8 nm.
[0149] Comparative Example 1
[0150] Example 1 was repeated, except that the amount of N-aminoethyl-γ-aminopropyltrimethoxysilane used in step 1) was 750 mg and 1000 mg, and other conditions remained unchanged. A stable dispersion could not be obtained, and a black precipitate appeared after being left for a period of time.
[0151] It can be seen from this that the amount of the modifier required by the present invention is controlled within the preferred range, and too little amount will not have any modification effect.
[0152] Comparative Example 2
[0153] Example 1 was repeated, except that the solvent ethanol in step 1) was replaced with water or a mixture of water and ethanol, and other conditions remained unchanged. Rod-shaped copper oxide nanoparticles were prepared, but stable ultra-small copper oxide methanol phase nanodispersions could not be prepared.
[0154] It can be seen from this that the preparation of copper oxide nanodispersion in methanol phase requires the selection of ethanol as the reaction solvent.
[0155] Comparative Example 3
[0156] Example 2 was repeated, except that the amount of potassium hydroxide used in step 1) was 2.0 g or 3.0 g, and other conditions remained unchanged. The obtained dispersion particles were severely agglomerated, and a stable monodispersed copper oxide nanodispersion could not be obtained.
[0157] It can be seen from this that the process for preparing copper oxide nanodispersions requires a suitable ratio of copper salt to alkali source.
[0158] Comparative Example 4
[0159] Example 2 was repeated except that the modification temperature in step 3) was 25° C. and other conditions remained unchanged. The obtained dispersion particles were severely agglomerated, and black precipitates appeared after being left for several hours, and a stable monodispersed copper oxide nanodispersion could not be obtained.
[0160] Obviously, the above embodiments and comparative examples of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the embodiments here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.
Claims
1. A method for preparing a monodisperse ultra-small nano copper oxide liquid phase dispersion, characterized in that: The steps include: 1) dissolving a copper salt precursor in a solvent to prepare a copper salt solution; dissolving an alkali in a solvent to prepare an alkali source solution; dissolving a surface modifier in a solvent to prepare a surface modifier solution; 2) mixing the copper salt solution and the alkali source solution to perform a hydrolysis reaction until the reaction solution turns black; 3) adding a surface modifier solution into the reaction solution for modification to obtain modified nano copper oxide particles; 4) The modified rice copper oxide particles are centrifugally washed and then dispersed in different solvents to obtain a monodisperse ultra-small nano copper oxide liquid phase dispersion.
2. The method for preparing the monodisperse ultrasmall nano copper oxide liquid phase dispersion according to claim 1, characterized in that: In step 1), the copper salt is selected from one or more of copper chloride, copper acetate, copper nitrate, copper sulfate, and copper acetylacetonate; Preferably, in step 1), the concentration of the copper salt precursor solution is 0.05-0.5 mol / L; more preferably, the concentration of the copper salt precursor solution is 0.2-0.5 mol / L.
3. The method for preparing the monodisperse ultrasmall nano copper oxide liquid phase dispersion according to claim 1, characterized in that: In step 1), the alkaline source is selected from one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, ammonia water, and urea; Preferably, in step 1), the concentration of the alkali source solution is 0.1-1 mol / L; preferably, the concentration of the alkali source solution is 0.4-1 mol / L.
4. The method for preparing the monodisperse ultra-small nano copper oxide liquid phase dispersion according to claim 1, characterized in that: In step 1), the molar ratio of the copper salt to the alkali salt is 0.4-0.6, preferably, the molar ratio of the copper salt to the alkali salt is 0.45-0.
55.
5. The method for preparing the monodisperse ultra-small nano copper oxide liquid phase dispersion according to claim 1, characterized in that: In step 1), the surface modifier is selected from one or more of polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide, polyethylene glycol, citric acid, sodium citrate, sodium dodecyl sulfate, phenyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-aminoethyl-γ-aminopropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, n-decanoic acid, lauric acid, myristic acid, stearic acid, behenic acid, oleic acid, sodium laurate, sodium stearate, and sodium oleate; Preferably, in step 1), the mass ratio of the surface modifier to the product is 10wt.%-300wt.%; preferably, the mass ratio of the surface modifier to the product is 30wt.%-200wt.%.
6. The method for preparing the monodisperse ultra-small nano copper oxide liquid phase dispersion according to claim 1, characterized in that: In step 1), the copper salt solution solvent is selected from one or more of water, methanol, ethanol, n-propanol, isopropanol, n-butanol, n-hexanol, n-octanol, acetone, ethylene glycol, glycerol, benzyl alcohol, n-hexane, cyclohexane, toluene, tetrahydrofuran, pyridine, ethyl acetate, and N-dimethylformamide.
7. The method for preparing the monodisperse ultra-small nano copper oxide liquid phase dispersion according to claim 1, characterized in that: In step 1), the alkali source solution solvent is selected from one or more of water, methanol, ethanol, n-propanol, isopropanol, n-butanol, n-hexanol, n-octanol, acetone, ethylene glycol, glycerol, benzyl alcohol, n-hexane, cyclohexane, toluene, tetrahydrofuran, pyridine, ethyl acetate, and N-dimethylformamide.
8. The method for preparing the monodisperse ultra-small nano copper oxide liquid phase dispersion according to claim 1, characterized in that: In step 1), the surface modifier solution solvent is selected from one or more of water, methanol, ethanol, n-propanol, isopropanol, n-butanol, n-hexanol, n-octanol, acetone, ethylene glycol, glycerol, benzyl alcohol, n-hexane, cyclohexane, toluene, tetrahydrofuran, pyridine, ethyl acetate, and N-dimethylformamide.
9. The method for preparing the monodisperse ultra-small nano copper oxide liquid phase dispersion according to claim 1, characterized in that: In step 1), the copper salt solution further includes a doping metal salt; the doping metal salt is selected from one or more of the following substances: lanthanum nitrate, gadolinium nitrate, cerium nitrate, yttrium nitrate, neodymium nitrate, scandium nitrate, zinc nitrate, magnesium nitrate, magnesium chloride, cobalt nitrate, nickel chloride, ferric chloride, ferrous chloride, ferrous sulfate heptahydrate, cerium nitrate hexahydrate, and cerium acetate; Preferably, in step 1), the molar percentage of the doped metal salt in the copper salt precursor is 0.5-10%; preferably, the molar percentage of the doped metal salt in the copper salt precursor is 3-10%.
10. The method for preparing the monodisperse ultra-small nano copper oxide liquid phase dispersion according to claim 1, characterized in that: In step 2), the reaction temperature of the copper salt solution and the alkali source solution is 40-100°C; preferably, the reaction temperature is 60-100°C; Preferably, in step 2), the reaction time is 1-15 min; preferably, the reaction time is 3-10 min; Preferably, in step 3), the modification temperature of the surface modifier is 40-100°C; preferably, the modification temperature is 60-100°C; Preferably, in step 4), the centrifugal speed is 5000-12000 rpm; more preferably, the centrifugal speed is 6000-10000 rpm; Preferably, in step 4), the dispersant is selected from one or more of the following substances: water, methanol, ethanol, n-propanol, ethylene glycol, glycerol, NN dimethylformamide, cyclohexane, n-hexane, toluene, xylene, petroleum ether 30-60°C, petroleum ether 60-90°C, dichloromethane, chloroform, tetrahydrofuran, naphtha, white oil, diesel, fish oil, methyl methacrylate, ethyl acetate, butyl acetate, acetone, cyclohexanone, methyl isobutyl ketone, and castor oil.
Citation Information
Patent Citations
Preparation method of nano copper oxide and application thereof
CN113247942A
Over-gravity field device of rotary bed for reinforcing transfer reaction
CN2221437Y
Process for making nano-sized and micro-sized precipitate particles
CN101523168A
Preparation method of copper oxide powder
CN105271358A
Method for preparing dispersion of superfine particle of copper oxide
JP2004323568A